The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1161/01.str.19.9.1101
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life 4 years after stroke.

Abstract: The quality of life for 46 stroke survivors under the age of 65 years in a stroke register was studied 4 years after their first stroke. A questionnaire covering four domains of life (working conditions, activities at home, family relationships, and leisure time activities) was used for investigation of the quality of life. The results showed that in spite of a good recovery in terms of discharge from the hospital, activities of daily living, and return to work, the quality of life of most patients (83%) had n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
142
5
11

Year Published

1993
1993
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(173 citation statements)
references
References 16 publications
10
142
5
11
Order By: Relevance
“…According to these results, we suggest that female patients and patients with lower income should be considered in a well-designed rehabilitation protocol to enhance their QOL. Our findings demonstrated that there was no association between HRQOL and age as previously reported (7,10,25); although some studies demonstrated a negative association between HRQOL and age (11,32,40), another study demonstrated a positive correlation (2). These controversial results may be ascribed to the different methodologies employed in each study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…According to these results, we suggest that female patients and patients with lower income should be considered in a well-designed rehabilitation protocol to enhance their QOL. Our findings demonstrated that there was no association between HRQOL and age as previously reported (7,10,25); although some studies demonstrated a negative association between HRQOL and age (11,32,40), another study demonstrated a positive correlation (2). These controversial results may be ascribed to the different methodologies employed in each study.…”
Section: Discussioncontrasting
confidence: 64%
“…For example, there are a limited number of studies investigating the effect of emotional status, functional health, and demographic properties on the QOL of patients with stroke (2,(8)(9)(10)(11). On the basis of previous reports of impairments in life quality of patients with stroke, we speculate that a variety of factors, such as sociodemographic, functional state, disability level, and emotional state, would have a significant influence on HRQOL of patients with stroke.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Bu benzerlik üst ve alt ekstremite Brunnstrom evreleri arasın-da da görülmüştür. İnme sonrası dönemde yaşam kalitesini etkileyen faktörleri araştıran çalışmaların sonuçları ile uyumlu olarak İEÖ 3,0 için hastaların yaşam kalitelerinin motor gelişim ve fonksiyonellik düzeyi arttıkça olumlu yönde etkilendiği gözlenmiştir (33)(34)(35).…”
Section: Discussionunclassified
“…Several studies have suggested that mental health and social support factors may also play an important role in the return to work. Two studies in particular demonstrated that living alone and depression at the time of follow up was associated with a decreased rate of return to work compared to age-matched stroke patients 10,50 , but by and large the areas remain relatively unexplored. Stroke patients often express feelings of hopelessness, helplessness, anxiety, and depression in addition to decreased social contact and growing isolation 48,49 .…”
Section: Section I: Introductionmentioning
confidence: 99%